Unicidade de hipersuperfícies capilares estáveis em uma bola - OLIVEIRA, Felipe Ferreira (2018)
In this work, we will study the result obtained by Guofang Wang and Chao Xia [14], which states that any immersed stable capillary hypersurface in a ball in spaces forms are totally umbilical. One of the main tools in solving the problem is the construction of a new Minkowski type formula. The approach of the test also works for closed hypersurfaces, that is, the work offers a new proof of the results of the uniqueness of Barbosa-do Carmo [4] and Barbosa-do Carmo-Eschenburg [5].